2020
DOI: 10.1097/aln.0000000000003189
|View full text |Cite
|
Sign up to set email alerts
|

Does Iso-mechanical Power Lead to Iso-lung Damage?

Abstract: Background Excessive tidal volume, respiratory rate, and positive end-expiratory pressure (PEEP) are all potential causes of ventilator-induced lung injury, and all contribute to a single variable: the mechanical power. The authors aimed to determine whether high tidal volume or high respiratory rate or high PEEP at iso-mechanical power produce similar or different ventilator-induced lung injury. Methods Three ventilatory str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 30 publications
3
65
1
7
Order By: Relevance
“…Indeed, for the same fluid input, the water retention in a 46-h experiment was twice as much important in animals treated with PEEP than without PEEP [54]. Similarly, for the same mechanical power, we found that the positive fluid balance was dramatically higher in animals treated with high levels of PEEP [55]. Nevertheless, fluid retention ceases when a new equilibrium is reached after 2-3 days [54].…”
Section: Origin Of Positive Fluid Balance and Modality Of Correctionsupporting
confidence: 62%
See 1 more Smart Citation
“…Indeed, for the same fluid input, the water retention in a 46-h experiment was twice as much important in animals treated with PEEP than without PEEP [54]. Similarly, for the same mechanical power, we found that the positive fluid balance was dramatically higher in animals treated with high levels of PEEP [55]. Nevertheless, fluid retention ceases when a new equilibrium is reached after 2-3 days [54].…”
Section: Origin Of Positive Fluid Balance and Modality Of Correctionsupporting
confidence: 62%
“…Fluid retention is the unavoidable "price" to pay to allow the use of positive-pressure mechanical ventilation. Importantly, the consequences of positive fluid balance are not limited to the lung (partly protected by the high intra-alveolar pressure) but also involve other organs which interstitial edema may deeply affect the function [55]. Consequently, excessive fluid retention must be ideally prevented, or corrected.…”
Section: Origin Of Positive Fluid Balance and Modality Of Correctionmentioning
confidence: 99%
“…Clinicians are used to use low tidal volumes (6 mL/kg, driving pressure < 14 cmH 2 O), and to maintain a viable CO 2 clearance, they ramp up the respiratory frequency. It is therefore of paramount importance to sensitize the intensivists to consider that high respiratory rate does injure the lung as it is part of the whole energy package delivered by the ventilator [11,25].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recent experimental data suggest that, indeed, this may be the case when high, VILI-inducing power levels are sustained for long enough periods. 9 Whatever its components, the same numerical value of total power calculated from airway pressure implies different hazards for different patients. The chest wall, for example, also requires energy and power to expand, and its compliance is degraded by massive obesity.…”
Section: Does Total Power Measured From Airway Pressure and Flow Paramentioning
confidence: 99%
“…It must be acknowledged that, although cumulative energy load and total power have been experimentally or clinically linked to VILI, exactly which delivered component or subcomponent of power correlates best with damage has not been clearly identified. 9,20,21 For example, it might be argued that only energy that relates to driving pressure or total elastic pressure {ie, the product of volume and absolute alveolar pressure, or (V T Â [DP + PEEP])} would best track lung stretch and VILI risk. 13 Alternatively, the total kinetic energy applied in excess of PEEP {ie, the product of volume and the sum of DP + P res .…”
Section: Cautions Regarding the Threshold-partitioned Modelmentioning
confidence: 99%